2021
DOI: 10.26855/ijfsa.2021.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Carcass Quality Characteristics of Indigenous Chickens and Their F1-Crosses with the Sasso Chicken Breed in Sheka Zone, South Western Ethiopia

Abstract: The study was conducted in three districts of Sheka zone in southern Ethiopia with the objective of comparing the carcass quality characteristics of indigenous chickens and their F1-crosses with Sasso chicken breed under traditional production system. One hundred eighty households were purposely selected who possess a minimum of three adult chickens. For the evaluation of carcass quality traits, 84 male chickens were used that have been drawn from both indigenous and F1-crossbred chickens. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
1
3
Order By: Relevance
“…Nevertheless, Motsepe et al [19] reported that the weight (yield) for the thigh and breast of Ovambo and Potchefstroom Koekoek indigenous chickens in South Africa exceeded those observed in the current study. The values observed in the present study were similar to those reported by Alemneh et al [17] regarding the weights of the heart and liver in indigenous chicken breeds in southwestern Ethiopia. Abdullah and Buchtova [30] reported higher yields for the heart, gizzard, and liver in organic commercial broiler chickens and conventional commercial broiler chicken carcasses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nevertheless, Motsepe et al [19] reported that the weight (yield) for the thigh and breast of Ovambo and Potchefstroom Koekoek indigenous chickens in South Africa exceeded those observed in the current study. The values observed in the present study were similar to those reported by Alemneh et al [17] regarding the weights of the heart and liver in indigenous chicken breeds in southwestern Ethiopia. Abdullah and Buchtova [30] reported higher yields for the heart, gizzard, and liver in organic commercial broiler chickens and conventional commercial broiler chicken carcasses.…”
Section: Discussionsupporting
confidence: 92%
“…The dressing percentage value for Goba (76.8%) and Agarfa (80.9%) indigenous chickens observed in our results showed a higher dressing percentage compared to that of Mogesse [16], who reported that the percentage value for local chicken ecotypes reared in Northwestern Ethiopia was 65.7%. However, Alemneh et al [17] reported lower values than the present results for local and F1-crosses in indigenous chicken breeds in southwestern Ethiopia. Moreover, the dressing percentage of an indigenous chicken in the present study was higher than that described by Magala et al [22] for free-range, run, and deep litter in local Ugandan chickens and Melesse et al [23] for commercial Koekoek chickens reared in Ethiopia under intensive management.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…As in the present trial, several authors have used SA chickens to produce F 1 with improved growth rate, feed intake, and hatchability compared to pure lines ( Alemneh et al, 2021 ; Bilalissi et al, 2022 ). Our findings showed that SA differed from BP and RM for all the growth curve parameters ( A, b , and k ) and derived indices as well as for the BW from posthatching to slaughtering.…”
Section: Discussionmentioning
confidence: 99%